Agroecological Business Opportunities for Attapeu, Lao PDR: Inclusive Business Models and Financing Strategies - Ou, Phichong; Charry, Andres; Teoh, Shwu Jiau; Chanthalath, Ammala; Douangsavanh, Somphasith; Sok, Raksa (WorldFish, 2024)
This report provides contextual information of the Attapeu province and Agroecological Living Landscape (ALL), followed by a brief analysis of some agricultural production systems with high agroecological potential: integrated rice-fish farming systems, organic rice production, red rice production, aquaculture, and vegetable production. This is followed by an assessment and prioritization of potential business opportunities derived from these production systems, comparing their performance in political, economic, social, technological, environmental and legal dimensions (PESTEL). By underscoring their main strengths, challenges and potential contribution with agroecological principles, this report attempts to provide the first step necessary for supporting local stakeholders in the co-development and promotion of the most feasible and potentially impactful business opportunities.